Aplikasi Teknik Statistik Dalam Evaluasi Kinerja Material Konstruksi Di Berbagai Kondisi Lingkungan - Bate'e, Elvin Krisman; Laoli, Excel Sahputra; Zebua, Dermawan; Halawa, Ignasia Hastuti; Ziliwu, Pasrah Iman Anugerah Putra; Halawa, Syukurman Jaya; Lase, Faerisman (CV. SINAR HOWUHOWU, 2024)
This study aims to evaluate the performance of construction materials using statistical techniques under various environmental conditions. The performance of construction materials used in infrastructure development is significantly influenced by environmental factors such as humidity, temperature, and soil pH. In this study, performance data of construction materials from different locations with varying environmental conditions are analyzed using statistical methods such as regression analysis, hypothesis testing, and analysis of variance (ANOVA). The analysis results show that environmental conditions have a significant impact on the durability and quality of construction materials, which affects the selection of materials for construction projects at specific locations. By using statistical techniques, this evaluation provides more accurate recommendations for the optimal selection of construction materials.